Microwave-assisted puffing of Dendrobium officinale for higher extraction rate of polysaccharides - Li, Yanhong; Wang, Zuoqiang; Li, Tingting; Bai, Xishan; Tian, Kai; Huang, Xiangzhong (Emirates Journal of Food and Agriculture, 2023)
In order to increase the extraction rate of Dendrobium officinale polysaccharides, microwave puffing was used to process its fresh stems and the processing parameters were optimized. Response surface methodology was used to analyze the effects of sample length (1–5cm), moisture content (15%–25%), microwave power (550–790 W), and microwave processing time (20–40 s) on the expansion ratio. The results showed that the optimized expansion ratio of 371.7% was achieved at the following conditions, i.e., sample length of 3.5 cm, moisture content of 23%, microwave power of 706 W, and processing time of 35 s. It was found that polysaccharides were extracted more readily from puffed D. officinale than from non-puffed D. officinale by 41.8%. Moreover, the bioactivities of polysaccharides from puffing D. officinale and non-puffing D. officinale were evaluated and compared in lipid peroxidation inhibition and anti-hyperglycemic assays. Keywords: Dendrobium officinale; Microwave puffing; Polysaccharides; Lipid peroxidation; Anti-hyperglycemic activity